HUBUNGAN PENGETAHUAN ORANG TUA DENGAN GIGI BERJEJAL DI SDN LAMSAYEUN ACEH BESAR - Zahara, Elfi; Reca, Reca (Jurnal Ilmiah Keperawatan, 2022)
Parents should play an active role in supervising their children's dental and oral health care. Based on preliminary data conducted on 12 students of SDN Lamsayeun Kec. Want Jaya Kab. Aceh Besar got the results that 9 of his teeth had crowding teeth. The purpose of this study was to determine the relationship of parental knowledge with crowding teeth in grade I, II and III children at SDN Lamsayeun, Want Jaya District, Aceh Besar district. This research is analytic with a cross sectional design, carried out on 8 to 12 November 2021. The population and sample are all students in grades I, II and III totaling 40 students and their parents. The results showed that students with dominant crowding had parents with sufficient knowledge as many as 9 respondents (100%). Meanwhile, students with dominant crowding had parents with poor knowledge of 13 respondents (54.2%) and students who did not experience dominant crowding had mothers with poor knowledge of 11 respondents (45.8%).The results of the chi-square statistical test obtained a value of p = 0.006 (p <0.005), Based on the results of the study, it can be concluded that there is a relationship between parental knowledge and crowding of children's teeth at SDN Lamsayeun Kec. Want Jaya Kab. Aceh Besar.